Dynamics and Energetics of Resistive, Thermally Conductive, and Radiative Plasma in Coronal Current Sheets due to Asymmetric External Perturbation - Mondal S.; Bairagi A.; Srivastava A.K. (My University, 2025)
We study the asymmetric interaction of wave-like velocity perturbation with a coronal current sheet (CS) in the presence of resistivity, thermal conduction (TC), and radiative cooling (RC). We analyze the dynamics and energetics of the CS in four cases, namely, (i) no energy loss, (ii) TC only, (iii) RC only, and (iv) TC+RC. Before fragmentation, thinning and elongation of the CS are found to be identical in all four cases and therefore independent of the presence or absence of energy loss effects. Onset times, corresponding Lundquist numbers, and aspect ratios suggest that TC advances the onset of fragmentation while RC has the opposite effect in comparison to the absence of energy losses. Reconnection takes place at a higher rate in the presence of TC and TC+RC in the tearing unstable CS. Speeds of plasmoids are also found to be higher under the effect of TC and TC+RC. In the presence of TC and TC+RC, average density becomes higher within the tearing unstable CS than in the other two cases. As expected, the estimated average temperature is increasing with the highest and lowest rates in the absence of energy losses and in the presence of both TC and RC, respectively. After the onset of fragmentation, the rate of decrement of average magnetic energy density and increment of average kinetic energy density becomes higher in the presence of TC and TC+RC than in the other two cases. Thus, we conclude that the presence of energy-loss mechanisms critically influences the dynamics, energetics, and plasmoid formation within a reconnecting coronal CS. © 2025. The Author(s). Published by the American Astronomical Society.